Apical Revascularization after Delayed Tooth Replantation: An Unusual Case - Marília Pacífico Lucisano; Paulo Nelson-Filho; Lea Assed Bezerra Silva; Raquel Assed Bezerra Silva; Fabricio Kitazono de Carvalho; Alexandra Mussolino de Queiroz (Hindawi Limited, 2016)
The aim of this paper is to present the clinical and radiological outcome of the treatment involving a delayed tooth replantation after an avulsed immature permanent incisor, with a follow-up of 1 year and 6 months. An 8-year-old boy was referred after dental trauma that occurred on the previous day. The permanent maxillary right central incisor (tooth 11) had been avulsed. The tooth was hand-held during endodontic therapy and an intracanal medication application with calcium hydroxide-based paste was performed. An apical plug with mineral trioxide aggregate (MTA) was introduced into the apical portion of the canal. When the avulsed tooth was replanted with digital pressure, a blood clot had formed within the socket, which moved the MTA apical plug about 2 mm inside of the root canal. These procedures developed apical revascularization, which promoted a successful endodontic outcome, evidenced by apical closure, slight increase in root length, and absence of signs of external root resorption, during a follow-up of 1 year and 6 months.